Effect of texture improvers on the organoleptic characteristics of a vegan product type of thick pasta sausage - Guadalupe Moyano, Verónica; Zamora Velásquez, Rodolfo; Ramón Casal, Tito; Rosciano Martínez, Carlo; Villegas Yánez, Santiago (Ingeniería Química y Desarrollo, 2024)
The growing vegan population in the world makes it necessary to develop better food products. The objective of this research is to produce a vegan thick pasta sausage product with acceptable organoleptic properties and high protein content. For this, vegan sausage formulas were prepared where the meat of animal origin was completely replaced with textured soy protein, using potato starch, carboxymethylcellulose (CMC) and wheat gluten as texture improvers; additionally, ingredients such as spices, vegetable, glutamate, nutritional yeast, etc. were used. For its evaluation, descriptive and hedonic sensory analysis was applied, the maximum shear force was determined using a texturometer and the protein content was quantified by proximal analysis. It was determined that the ideal proportion of additives is 20% wheat gluten, 0-3% potato starch and 0-0.3% CMC, since in this way the highest organoleptic acceptance values were obtained, without differing too much from an existing sausage type vegan commercial product as control sample. In addition, it was possible to improve the texture to values of 911.50 + 93.00g (F1) and 861.89 + 66.17g (F4), superior to other developments of vegan sausages from bibliography. Finally, it was determined that the protein content of the two formulas developed (F1 21.99%, F4 19.57%) is higher than that of a commercial vegan product (16%) and that of the original Manabí sausage (16%). In conclusion, the elaboration of a vegan product type sausage of thick pasta is feasible maximizing its organoleptic properties thanks to the use of the three texture improvers, especially wheat gluten.